Thoughts on religion - Shattock, Samuel, 1853-1924 (Routledge revivals., 2015)
This book, first published in 1926, is a collection of the original thoughts of Samuel George Shattock on religious matters. Shattock recorded his thoughts on religion throughout his life. This title brings together what Shattock himself felt to be his most important ideas on theology. Thoughts on Religion will be of interest to students of religion and philosophy.